OECD economic outlook. Volume 2016 Issue 2 (Paris, 2016)
"The OECD Economic Outlook is the OECD's twice-yearly analysis of the major economic trends and prospects for the next two years. The Outlook puts forward a consistent set of projections for output, employment, prices, fiscal and current account balances. Coverage is provided for all OECD member countries as well as for selected non-member countries. This issue includes a general assessment, a special chapter on promoting productivity and equality, a chapter summarising developments and providing projections for each individual country and a statistical annex"